Across‐model spread and shrinking in predicting peatland carbon dynamics under global change. Issue 10 (26th February 2023) - Hou, Enqing; Ma, Shuang; Huang, Yuanyuan; Zhou, Yu; Kim, Hyung‐Sub; López‐Blanco, Efrén; Jiang, Lifen; Xia, Jianyang; Tao, Feng; Williams, Christopher; Williams, Mathew; Ricciuto, Daniel; et al.
Abstract: Large across‐model spread in simulating land carbon (C) dynamics has been ubiquitously demonstrated in model intercomparison projects (MIPs), and became a major impediment in advancing climate change prediction. Thus, it is imperative to identify underlying sources of the spread. Here, we used a novel matrix approach to analytically pin down the sources of across‐model spread in transient peatland C dynamics in response to a factorial combination of two atmospheric CO2 levels and five temperature levels. We developed a matrix‐based MIP by converting the C cycle module of eight land models (i.e., TEM, CENTURY4, DALEC2, TECO, FBDC, CASA, CLM4.5 and ORCHIDEE) into eight matrix models. While the model average of ecosystem C storage was comparable to the measurement, the simulation differed largely among models, mainly due to inter‐model difference in baseline C residence time. Models generally overestimated net ecosystem production (NEP), with a large spread that was mainly attributed to inter‐model difference in environmental scalar. Based on the sources of spreads identified, we sequentially standardized model parameters to shrink simulated ecosystem C storage and NEP to almost none. Models generally captured the observed negative response of NEP to warming, but differed largely in the magnitude of response, due to differences in baseline C residence time and temperature sensitivity of decomposition. While there was a lack of response of NEP to elevated CO2 (eCO2 ) concentrations in the measurements, simulated NEP responded positively to eCO2 concentrations in most models, due to the positive responses of simulated net primary production. Our study used one case study in Minnesota peatland to demonstrate that the sources of across‐model spreads in simulating transient C dynamics can be precisely traced to model structures and parameters, regardless of their complexity, given the protocol that all the matrix models were driven by the same gross primary production and environmental variables. Abstract : A novel matrix approach is developed to analytically pin down the sources of across‐model spread in transient peatland carbon dynamics in response to a factorial combination of two atmospheric CO2 levels and five temperature levels. Spread in ecosystem carbon storage is mainly due to inter‐model difference in baseline carbon residence time, while spread in net ecosystem production (NEP) is mainly due to difference in environmental scalar. Based on the sources of spreads identified, model parameters are sequentially standardized to shrink simulated ecosystem carbon storage and NEP to almost none.